2017
DOI: 10.3389/fpls.2017.00356
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into microRNA156 Role in Salinity Stress Responses of Alfalfa

Abstract: Salinity is one of the major abiotic stresses affecting alfalfa productivity. Developing salinity tolerant alfalfa genotypes could contribute to sustainable crop production. The functions of microRNA156 (miR156) have been investigated in several plant species, but so far, no studies have been published that explore the role of miR156 in alfalfa response to salinity stress. In this work, we studied the role of miR156 in modulating commercially important traits of alfalfa under salinity stress. Our results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 101 publications
5
63
0
Order By: Relevance
“…Several studies have suggested role for miR156 during environmental stress conditions in various plant species [68][69][70][71]. In this study, the target of miR156 was SPL TF which may alter expression of downstream genes.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have suggested role for miR156 during environmental stress conditions in various plant species [68][69][70][71]. In this study, the target of miR156 was SPL TF which may alter expression of downstream genes.…”
Section: Discussionmentioning
confidence: 73%
“…Eighty-two unique transcripts were found from the salt-stressed seedlings of alfalfa by sampling at different time intervals from 10 min to 24 h, including 24% that were proteins related to plant metabolism and 9% that were related to abiotic stress [87]. Arshad et al [88] found that the over-expression of microRNA156 in alfalfa resulted in increased biomass production, stem number, concentration of crude protein, and reduced uptake of Na + under salt stress. In another transcriptome study, there were 876 and 1303 differentially expressed genes (DEGs) under salt stress in the root tissues of one-week-old seedlings in salt-intolerant and tolerant alfalfa genotypes respectively, with 604 DEGs specific to the salt-tolerant type [83].…”
Section: Proteome and Transcriptomic Analysesmentioning
confidence: 99%
“…Intriguingly, it has recently become apparent that the modulation of these epigenetic factors may, at least in some cases, translate into improved abiotic stress tolerance. For instance, the overexpression of miR169, miR408, and miR319, respectively, has been found to enhance abiotic stress tolerance in various plant species (Hajyzadeh, Turktas, Khawar, & Unver, ; Yang et al, ; Zhang et al, ; Zhou et al, ), and the overexpression of miR156 has also recently been found to improve drought and salinity stress tolerance in alfalfa (Arshad, Feyissa, Amyot, Aung, & Hannoufa, ; Arshad, Gruber, Wall, & Hannoufa, ). Although miR156's role in drought tolerance in alfalfa appears to be related to its transcript cleavage‐based silencing of the SPL13 gene (Arshad et al, ), a further unraveling of the interplay between these diverse regulatory mechanisms is going to be a necessity for gaining a full understanding of the molecular pathways driving abiotic stress response in plants, and also for the successful design of biotechnological strategies with which to improve this trait in the future.…”
Section: Introductionmentioning
confidence: 99%